Case Study of Recognition of Land Rights of Dayak Customary Law Community in Central Kalimantan in Constitutional Court Decision Number 35/PUU-X/2012 - Aulia, Stefani Dwi; Budi, Idzni; Antarikza, Lintang; Dwi, Stefani; Surya, Steven (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2024)
Agrarian Law is regulated in Law Number 5 of 1960 concerning the Principles of Agrarian Law (UUPA) which regulates the control, ownership, allocation, use and control of land use aimed at the greatest prosperity of the people. Based on Article 3 of Law Number 5 of 1960, the recognition of customary rights is limited to two things, namely regarding its existence and implementation. The method used in this study is the normative legal research method by approaching legislation and conceptually using primary, secondary and tertiary legal materials. One of the problems regarding the recognition of customary land rights is customary land rights that occur in Central Kalimantan Province. The existence of the Dayak Customary Council of Central Kalimantan Province as a customary institution that has been emphasized in Regional Regulation Number 16 of 2008 concerning Dayak Customary Institutions in Central Kalimantan, is expected to be able to maintain, preserve and defend the values ​​of customary law. Especially after the Constitutional Court Decision Number 35/PUU-X/2012, which confirmed that Customary Forests are Forests located in customary areas, and are no longer State Forests. Likewise with the Regulation of the Minister of Home Affairs Number 52 of 2014 concerning Guidelines for the Recognition and Protection of Customary Law Communities, which also provides space for recognition of customary law communities. This regulation certainly provides hope for customary law communities to obtain recognition and protection of the rights they have, namely Customary Territory, Customary Law, Wealth and/or Customary Objects and Institutions/Government Systems.